2009
DOI: 10.1158/0008-5472.can-08-2008
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Linkage Analysis of TMPRSS2-ERG Fusion in Familial Prostate Cancer

Abstract: Fusion of the 5 ¶-untranslated region of androgen-regulated TMPRSS2 promoter with ETS transcription factor family members is found frequently in prostate cancers, and recent work suggests that the most common TMPRSS2-ERG fusion is associated with an aggressive clinical phenotype compared with fusion-negative prostate cancer. Thus far, analysis of the fusion has been limited to sporadic cases of prostate cancer. In the current study, we explore for an enrichment of TMPRSS2-ERG fusion in familial prostate cancer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 38 publications
3
24
0
1
Order By: Relevance
“…In our pilot study, no significant association was identified between ERG status and tumour stage in a limited cohort of patients (16). However, ERG rearrangement was found to be positively correlated with advanced tumour stage in a larger cohort of samples in this study, which is consistent with previous reports (28)(29)(30)(31). Overall, ERG rearrangement tends to be positively associated with advanced pathological stage, which has been further verified in a meta-analysis of 34 series (32).…”
Section: Discussionsupporting
confidence: 91%
“…In our pilot study, no significant association was identified between ERG status and tumour stage in a limited cohort of patients (16). However, ERG rearrangement was found to be positively correlated with advanced tumour stage in a larger cohort of samples in this study, which is consistent with previous reports (28)(29)(30)(31). Overall, ERG rearrangement tends to be positively associated with advanced pathological stage, which has been further verified in a meta-analysis of 34 series (32).…”
Section: Discussionsupporting
confidence: 91%
“…Both TMPRSS2 and ERG are located on chromosome 21q22 with about 2.8 Mb of distance and about 40% to 60% of all PCas harbor their fusion. In our previous study, we found evidence for an inherited susceptibility for TMPRSS2-ERG fusion-positive PCa and obtained several candidate loci at 5q14, 9q21, 10q26, 11q26, 12q21, 13q12, 18q, and Xq27 by linkage analysis (8). We hypothesize that susceptibility for the oncogenic fusion could be explained by a generally elevated chromosomal instability with subsequent selection for growth advancing rearrangements.…”
Section: Introductionmentioning
confidence: 84%
“…The index patients' mean age at diagnosis was 62.9 y (range, 40-80 y). For the sequencing of candidate genes, index probands were chosen from 10 independent families with at least two TMPRSS2-ERG fusion-positive PCa cases that were used for a genomewide linkage analysis (8). Two additional fusion-positive index probands were screened, of which the fusion status of affected relatives was unknown.…”
Section: Methodsmentioning
confidence: 99%
“…Although TMPRSS2 -ERG fusion has typically been reported as prevalent in 40 -50% of prostate tumours, the range has varied by as much as 25 -60% (Nam et al, 2007;Setlur et al, 2008;Sun et al, 2008;Yoshimoto et al, 2008;Hofer et al, 2009;Mosquera et al, 2009). The techniques used for TMPRSS2 -ERG detection, novel potential fusion products and genetic differences in population cohorts may account for these discrepancies.…”
mentioning
confidence: 99%